2000
DOI: 10.1128/jvi.74.14.6684-6688.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Late Gene Expression Does Not Require a Rev-Like Nuclear RNA Export Pathway

Abstract: Adenovirus late mRNA export is facilitated by viral early proteins of 55 and 34 kDa. The 34-kDa protein contains a leucine-rich nuclear export signal (NES) similar to that of the human immunodeficiency virus Rev protein. It was proposed that the 34-kDa protein might facilitate the export of adenovirus late mRNA through a Rev-like NES-mediated export pathway. We have tested the role of NES-mediated RNA export during adenovirus infection, and we find that it is not essential for the expression of adenovirus late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
7
26
0
Order By: Relevance
“…A subset of the short-lived cellular mRNAs characterized by the presence of AU-rich sequences in their 3Ј untranslated regions have been reported to leave the nucleus by the exportin 1 pathway (39). Previous studies have demonstrated that inhibition of exportin 1 does not impair synthesis of viral late protein (2,72) or of export of viral late mRNAs (35), despite the exportin 1-dependent shuttling of the E1B protein between the nucleus and cytoplasm (27,29,57). Rather, data reported here implicate Nxf1 in export of these viral mRNAs from the nucleus to the cytoplasm: synthesis in Ad5-infected cells of an interfering RNA that reduced the concentration of Nxf1, but not of a control nontargeting interfering RNA, results in decreased efficiency of export of viral late mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of the short-lived cellular mRNAs characterized by the presence of AU-rich sequences in their 3Ј untranslated regions have been reported to leave the nucleus by the exportin 1 pathway (39). Previous studies have demonstrated that inhibition of exportin 1 does not impair synthesis of viral late protein (2,72) or of export of viral late mRNAs (35), despite the exportin 1-dependent shuttling of the E1B protein between the nucleus and cytoplasm (27,29,57). Rather, data reported here implicate Nxf1 in export of these viral mRNAs from the nucleus to the cytoplasm: synthesis in Ad5-infected cells of an interfering RNA that reduced the concentration of Nxf1, but not of a control nontargeting interfering RNA, results in decreased efficiency of export of viral late mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This cellular protein contains an NES that is recognized by exportin 1 and binds to the human HuR protein, which has been identified as an export adaptor for certain unstable cellular mRNAs (12,39). Nevertheless, exportin 1 is not responsible for export of viral late mRNAs: treatment of infected cells with leptomycin B under conditions that blocked accumulation of the E1B 55-kDa protein in the cytoplasm had no impact on synthesis of viral late proteins (17,72). Furthermore, a cell-permeative peptide containing the HIV-1 Rev NES, but not an inactive derivative, significantly reduced the cytoplasmic accumulation of the E1B 55-kDa protein and inhibited its shuttling between the nucleus and cytoplasm (35), but it did not impair the efficiency with which processed major late (ML) penton or fiber mRNAs were exported from the nucleus (35).…”
mentioning
confidence: 99%
“…On the other hand, it has also been reported that the E4 Orf 6 NES failed to direct efficient export of a heterologous protein and that export of this E4 protein is insensitive to leptomycin B (26,58). Regardless of whether the E4 Orf 6 protein leaves the nucleus via the exportin 1 pathway, there is clear evidence that this export receptor does not mediate export of viral late mRNAs: the inhibition of exportin 1 by leptomycin B or an NES containing peptide had no effect on synthesis of viral late proteins (15,78) or viral late mRNA export (34).…”
mentioning
confidence: 96%
“…It has also been reported that the E4 Orf 6 protein contains a similar NES necessary for exportin-dependent shuttling of the E1B 55-kDa-E4 Orf 6 protein complex and sufficient to allow export when fused to an heterologous protein (24). The specific inhibitor of exportin 1, leptomycin B, has been observed to inhibit shuttling of this E4 protein substantially (78). On the other hand, it has also been reported that the E4 Orf 6 NES failed to direct efficient export of a heterologous protein and that export of this E4 protein is insensitive to leptomycin B (26,58).…”
mentioning
confidence: 99%
“…E4orf6 is a nuclear protein containing both nuclear localization and nuclear retention signals that are believed to be responsible for targeting E4orf6 and E4orf6/E1B55K complexes to the nucleus (Goodrum et al 1996;Orlando and Ornelles 1999;Nevels et al 2000). In addition, both E4orf6 and E1B55K have nuclear export signals, and several groups have shown they can shuttle between the nucleus and the cytoplasm (Dobbelstein et al 1997;Weigel and Dobbelstein 2000;Rabino et al 2000;Dosch et al 2001).…”
mentioning
confidence: 99%